The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1001/jama.1980.03310200043024
|View full text |Cite
|
Sign up to set email alerts
|

Cost of a Home Parenteral Nutrition Program

Abstract: We analyzed the costs to a hospital of providing complete home parenteral nutrition (HPN) services for eight patients. Identified cost components include patient training, equipment, supplies, and follow-up. The average annual cost of maintaining parenteral nutrition at home was 73% lower than it would have been in the hospital. The establishment of private companies to provide patients with HPN supplies and services will reduce the financial burden of HPN programs for hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The demographics of these patients were similar to those included in the cost analysis part of the study with respect to age (median [range]: HEN: 51 [24 to 59] years; HPN: 56 [25 to 74] years), sex distribution (HEN: men, 3; women, 7; HPN: men, 8; women, 14), and indication for therapy. The indication for therapy was self-reported with the HPN patients citing short bowel syndrome (17), inflammatory bowel disease (10), Behqet's disease (1), radiation enteritis (1), and gastrointestinal motility disorders (4). Because patients checked more than one reason, the numbers added up to more than 22 in the HPN group.…”
Section: Assessment Of Problems Relating To the Administration Of Hpementioning
confidence: 99%
“…The demographics of these patients were similar to those included in the cost analysis part of the study with respect to age (median [range]: HEN: 51 [24 to 59] years; HPN: 56 [25 to 74] years), sex distribution (HEN: men, 3; women, 7; HPN: men, 8; women, 14), and indication for therapy. The indication for therapy was self-reported with the HPN patients citing short bowel syndrome (17), inflammatory bowel disease (10), Behqet's disease (1), radiation enteritis (1), and gastrointestinal motility disorders (4). Because patients checked more than one reason, the numbers added up to more than 22 in the HPN group.…”
Section: Assessment Of Problems Relating To the Administration Of Hpementioning
confidence: 99%
“…1,2 Previous cost analyses have concluded that home PN reduces costs by 65%-81% when compared with hospital-based PN. [2][3][4][5][6][7] However, these estimates differ in the components of cost they included, the assumptions they made, and in the analytic perspective they assumed. For example, Curtas et al estimated personnel costs of home PN delivery but not the overall costs of care.…”
mentioning
confidence: 99%
“…Maximum adaptation can only be reached when early enteral nutrition acts as a potent stimulator of mucosal growth [25]. The period of adaptation typically lasts for about 1 year in adults and up to 4 years in children [26,27]. It is commonly believed that patients will remain on TPN if enteral autonomy has not been regained by that time.…”
Section: Early Therapymentioning
confidence: 99%